Collaborative Alignment: a framework for community-based collaboration for natural resource management, environmental policy decisions, and locally-led climate action - Walker, Gregg; Severson, Gary; Daniels, Steve (Frontiers in Communication, 2023)
This essay introduces the Collaborative Alignment Framework (CA) and proposes its suitability for empowering and engaging communities as they address issues related to SDG 15. The fifteenth Sustainable Development Goal is concerned with protecting, restoring and promoting sustainable use of terrestrial ecosystems; managing forests sustainably; combating desertification, and stopping and reversing land biodiversity loss. Doing so necessarily involves communities and the parties that have a lot at stake related to environmental safeguards and management practices. Consequently, the discussion of Collaborative Alignment occurs in the following steps: First, it situates CA in the community-based forest collaborative movement in the United States, a movement that emerged in the forestry sector in the 1990s (Weber, 2003). Second, the essay addresses the foundations of CA. Third, CA is explained. Fourth, case examples of CA applications are featured. Lastly, the essay presents the relevance of Collaborative Alignment to "locally-led adaptation," a community and place-based approach for addressing climate change (and SDG 13).